PERSEPSI GURU TERHADAP PENGGUNAAN MEDIA KONKRET DALAM PEMBELAJARAN BILANGAN CACAH DI SD - Nurzaki, Hasna Amelia; Putri, Hafiziani Eka; Hadizah, Salsa Nurul; Wulandari, Windy; Azka, Hilwah; Syadili, Ahmad (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to explain teachers’ perspectives on the use of concrete media in teaching whole numbers at the elementary school level. The research employed a descriptive qualitative approach, with data collected through semi-structured interviews and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that teachers believe concrete media help students understand abstract concepts, improve concentration, and enhance learning engagement. However, teachers also face several challenges, such as limited teaching aids, time constraints, and difficulties in helping students transfer understanding from concrete objects to mathematical symbols. To address these challenges, teachers utilize simple and readily available materials, plan lessons carefully, and involve students in the creation and use of the learning media. In conclusion, while concrete media are perceived as effective in supporting mathematics learning, their optimal implementation requires adequate resources, proper planning, and active student involvement.